5GtoB: innovation path under the perspective of digital transformation - Chao LING (Dianxin kexue, 2022)
Two different business models of 5GtoB were analyzed, the current toB business tend to adopt the project business model rather than the product business model, which will become an important obstacle in the large-scale development of 5GtoB.On this basis, three types of innovation modes in the current wave of digital transformation were analyzed, including process innovation, product innovation and service innovation, and integrating product innovation is the key path for 5GtoB to realize product business model and large-scale development, and service innovation will further expand the application field of 5GtoB and drive the development of platform.